COMPARISON OF CARIES INDEX IN PERMANENT DENTITION UNDER ACTIVE UKGS AND NON-ACTIVE UKGS Observation on elementary school sixth grade students or of the same level in Puskesmas Kertak Hanyar Kecamatan Kertak Hanyar Kabupaten Banjarâs working area - Tanu, Lenny Octaviani; Adhani, Rosihan; Widodo, Widodo (FKG Unlam, 2017)
Background : UKGS is an effort to improve oral and dental health of students in school. UKGS program has been running since 1951, but the dental health of elementary school students is yet to be satisfactory. 2013th RISKESDAS reports show that 36,1% citizens living in Kalimantan Selatan had oral health problems, and the prevalence of people who had oral health problems in Kabupaten Banjar is 48,6% but only 13,8% received treatments and cares from dental staffs. Purpose : The purpose of this study was to assess the comparison of caries index in permanent dentition of elementary school students under active UKGS and non-active UKGS. Methods : This was a quantitative analytic study using cross sectional approach. The samples were 100 students picked using proportionate random sampling. Data were obtained from DMF-T index assessments. Results : The caries indexes of students under active UKGS and non-active UKGS were 1,36 (low) and 2,72 (moderate) respectively. Conclusion : There was a significant comparison (p<0,05) of DMF-T index in permanent dentition of students under active UKGS and non-active UKGS in Puskesmas Kertak Hanyar Kecamatan Kertak Hanyar Kabupaten Banjarâs working area.